Attitudes, Subjective Norms, Perceived Behavioral Control, And Intention towards Breastfeeding Among Bangladeshi Primiparous Pregnant Women - บีกัม โมชามเม็ด เจนาป; จินตะเวช อุษณีย์; ศรีภูษณาพรรณ อัจฉราภรณ์ (Nursing Journal CMU, 2018)
Breastfeeding is a recognized by the World Health Organization as providing high nutritional values for child growth while helping the development of a child’s immune system. The aim of this descriptive correlational research was to study attitudes, subjective norms, perceived behavioral control, and intention towards breastfeeding among primiparous pregnant women in Bangladesh. The sample consisted of 120 primiparous pregnant women who visited the ante natal unit at the Comilla Medical College Hospital, Bangladesh, from April 2015 to May 2015. The research instrument was a questionnaire which investigated attitudes, subjective norms, perceived behavioral control, and intention towards breastfeeding. The overall reliability of the questionnaire, using the Cronbach’s alpha coefficient, was .79. Data were analyzed using descriptive statistics. The results revealed that: 1. 54.17% of the sample showed positive attitudes towards breastfeeding and higher than the mean score. 2. 81.7% reported that persons about whose opinion they cared was their hospital nurse. More than half of the sample (52.50%) reported that their doctor and half of the sample (50%) indicated the baby’s father were influential in their intention to breastfeed. 3. Seventy-nine point one seven percent of the sample showed high levels of perceived behavior control. 4. The whole sample (100%) demonstrated an intention to breastfeed. 5. Relationship between attitudes, subjective norms, and perceived behavioral control; and intention towards breastfeeding could not be analyzed seen the whole sample indicated an intention to breastfeed. The findings of this study provide preliminary data suggesting that all samples of primiparous Bangladeshi pregnant women have an intention to breastfeed. Further study is recommended to examine whether there is a correlation between breastfeeding intention and practice.